Cleidocranial dysplasia: A report of two cases - D N Mehta; R V Vachhani; M B Patel (Wolters Kluwer Medknow Publications, 2011)
Cleidocranial dysplasia (CCD) is an autosomal dominant disorder that presents with skeletal dysplasia. It commonly presents with significant dental problems such as retention of multiple deciduous teeth, impaction or delay in eruption of permanent teeth, and often with the presence of supernumerary teeth. We report two cases showing clinical and radiographic features of CCD.